Otogenic Brain Abscess: A retrospective study of 10 patients and review of the literature - Asma A,; Hazim MYS,; Marina MB,; Suraya A,; Azizi AB,; Mazita A,; Norlaili MT,; L Saim,; Zahiruddin, (Penerbit UKM, 2007)
Proper management of chronic otitis media may reduce the incidence of otogenic brain abscess. The aim of this study was to describe the clinical profile, treatment and surgical outcome of patients presenting with otogenic brain abscess. The medical record of patients in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) with otogenic brain abscess were retrospectively analyzed from January 1997-January 2006. Within this period we had approximately 10,800 of follow up cases of chronic otitis media (COM) in our clinic. Ten patients (2 females, 8 males) with an average age of 42 (age range 11 to 69 years) were identified with otogenic brain abscess and included in this study. The mean follow-up period was 14 months. All patients had cholesteatoma. All patients had a history of chronic ear discharge, headache, otalgia and fever. Six of the 10 patients had cerebellar abscess and 4 had temporal lobe abscess. Cerebellar signs were present in 3 patients. All the patients were treated with broad-spectrum antibiotics. In 5 patients, mastoid exploration was the primary surgical treatment and the brain abscesses were treated conservatively. In the other 5 patients, craniotomy and drainage were performed followed by mastoid exploration when their neurological conditions had stabilized. All our patients had uneventful recovery. There were no permanent cerebellar signs during the follow up and no mortality reported in our series. In this series we demonstrated that early diagnosis and proper treatment of otogenic abscess leads to good neurological outcome